Menggagas Pembelajaran PAI Berbasiskan Multikultural - Moh. Nasrul Amin (Darajat: Jurnal Pendidikan Agama Islam, 2020)
Indonesia is known as a pluralistic society (pluralistic society). The plurality of Indonesian society can be seen from the diversity of ethnicities, cultures, ethnicities, religions and even schools of thought in religion and so on. From this plurality, it provides opportunities for the community to potential in a positive direction and will also become a negative potential. Responding to the existing potential, it is certain that the Indonesian people hope that this diversity will become a potential that leads to positive things. Therefore, to achieve positive things from plurality, special attention is needed, especially in the field of education, in the field of education, it must pay attention to differences and even provide insights related to multiculturalism itself. from here, Islamic Religious Education has an important role in efforts to provide multicultural-based learning services. To realize multicultural-based learning, there are at least five things in the multicultural-based PAI learning component, namely: first is the aspect of learning objectives, learning objectives are directed at knowledge and understanding of the reality of diversity that exists in society and especially the diversity of school members themselves. Second, namely learning resources and materials, learning resources and learning materials PAI should match the color of the learning sources as well as the material by providing various references and also, for example, in the material of fiqh giving views from several schools of thought. The third is learning strategies and models, strategies and learning models must provide opportunities for students to become subjects in seeking knowledge from various references through interactive learning strategies, cooperative learning, quantum teaching, quantum learning, contextual teaching learning and so on. The fourth is learning media, this learning media can use electronic-based media, for example through television which contains news about people's lives that are different from where students live, then community phenomena related to the diversity phenomenon can be used as material for analysis in the classroom. The fifth or the last one is learning evaluation, this learning evaluation focuses on the process of student knowledge and understanding of the differences that exist in students and Indonesian society